2013
DOI: 10.2147/ndt.s47293
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and imaging findings in a case of Capgras syndrome

Abstract: Capgras syndrome consists of the delusional belief that a person or persons have been replaced by doubles or impostors. It can occur in the context of both psychiatric and organic illness, and seems to be related to lesions of the bifrontal and right limbic and temporal regions. Indeed, magnetic resonance imaging has revealed brain lesions in patients suffering from Capgras syndrome. This case study reports the findings of a thorough diagnostic evaluation in a woman suffering from Capgras syndrome and presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…A principal alteração encontrada através da sequência T2-wieghted-fluid-attenuated inversion recovery (FLAIR) é a desconexão entre a região occipital e o hipocampo, além disso ocorre hiperintensidade nas regiões frontais e occipitais, substância branca temporal subcortical e no centro oval, além de uma atrofia global do cérebro. 1,7,8 O tratamento se baseia na contenção dos sintomas psicóticos com antipsicóticos, muitas vezes associado a antidepressivos, tendo uma resposta satisfatória em aproximadamente 65% dos casos tratados. Outras formas de tratamento proposto são o uso de benzodiazepínicos, lítio, antiepiléticos, eletroconvulsoterapia e cirurgias.1 , 9 A raridade dos casos em literatura, tendo aproximadamente 258 casos descritos nos últimos 52 anos, corroborado pela ausência da mesma no manual diagnóstico de doenças mentais (DSM-V) e associado à possível gravidade da doença com casos de homicídios relatados devido aos sintomas torna o estudo da síndrome de extrema importância para que seja estabelecidos critérios para melhor diagnosticar e prever o aparecimento dos sintomas, além de estratégias terapêuticas condizentes e eficazes.…”
Section: Discussionunclassified
“…A principal alteração encontrada através da sequência T2-wieghted-fluid-attenuated inversion recovery (FLAIR) é a desconexão entre a região occipital e o hipocampo, além disso ocorre hiperintensidade nas regiões frontais e occipitais, substância branca temporal subcortical e no centro oval, além de uma atrofia global do cérebro. 1,7,8 O tratamento se baseia na contenção dos sintomas psicóticos com antipsicóticos, muitas vezes associado a antidepressivos, tendo uma resposta satisfatória em aproximadamente 65% dos casos tratados. Outras formas de tratamento proposto são o uso de benzodiazepínicos, lítio, antiepiléticos, eletroconvulsoterapia e cirurgias.1 , 9 A raridade dos casos em literatura, tendo aproximadamente 258 casos descritos nos últimos 52 anos, corroborado pela ausência da mesma no manual diagnóstico de doenças mentais (DSM-V) e associado à possível gravidade da doença com casos de homicídios relatados devido aos sintomas torna o estudo da síndrome de extrema importância para que seja estabelecidos critérios para melhor diagnosticar e prever o aparecimento dos sintomas, além de estratégias terapêuticas condizentes e eficazes.…”
Section: Discussionunclassified
“…When the onset of DMS symptoms occurs after the age of 65, it could be suggestive of a degenerative neurocognitive condition. Therefore, a detailed neurological examination and relevant tests including electroencephalogram (EEG), magnetic resonance imaging (MRI) [ 16 - 17 ], or other investigations are an essential part of the clinical workup [ 18 ]. There are many case reports of early-onset psychosis with DMS which highlights the risks of violence and homicide.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have provided evidence that CD can be associated to gross brain damage ( Edelstyn and Oyebode, 1999 , Huang et al, 1999 , Breen et al, 2000a , Josephs, 2007 ). Bilateral or right-hemisphere abnormalities, particularly in the frontal region and in the temporal and/or parietal lobes, have been reported with visual inspection of MRI or CAT scans ( Lewis, 1987 , Hirstein and Ramachandran, 1997 , Edelstyn et al, 2001 , Breen et al, 2002 ; Devinsky, 2009 , Luca et al, 2013 ). The importance of the right frontal lobes in many different forms of delusion, including CD has been previously discussed ( Coltheart, 2007 , Devinsky, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…With visual inspection of MRI, Edelstyn et al (2001) reported a patient with right hemisphere subcortical white-matter pathology in the frontal and parietal lobes and a diagnosis of vascular cognitive impairment. Another study ( Luca et al, 2013 ) reported a patient with lesions in the frontal subcortical white matter bilaterally. It is difficult to compare these previous studies with ours.…”
Section: Discussionmentioning
confidence: 99%